THE EFFECTIVENESS OF ENVIRONMENTAL FUNCTION SPENDING IN IMPROVING WASTE MANAGEMENT EFFICIENCY IN INDONESIA - Lestari, Ayu; Ningsih, Sri (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
Waste management remains a serious challenge in Indonesia’s pursuit of sustainable environmental development. Amid limitations in infrastructure, institutional coordination, and policy consistency, the effectiveness of local government spending on environmental functions plays a crucial role in promoting waste management efficiency and improving service delivery. This study aims to analyze the effect of environmental function spending on the efficiency of waste management in Indonesia. A quantitative approach is employed using panel data from 34 provinces over the period 2019 to 2023, enabling the assessment of temporal and cross-regional variations. The analysis is conducted using panel regression with a random effects model approach, selected based on statistical tests to account for unobserved heterogeneity among provinces. The results show that environmental function spending has a positive and significant effect on waste management efficiency. This implies that a greater budget allocation to environmental functions leads to higher efficiency in waste management by local governments, likely through improved facilities, human resources, and program implementation. These findings underscore the importance of optimizing local budget policies in the environmental sector to support more effective and sustainable waste management systems, as well as to meet broader development goals related to public health, environmental quality, and climate resilience.